NTeALan - AI/NLP/NLU Platforms For Sharing and Leveraging African Language Resources For Education In Africa - (:unkn) unknown (My University, 2019)
Among the challenges the African continent faces the issue of safeguarding and enhancing its cultural and linguistic inheritance. Created in 2017, the NTeALan project aims at setting up intelligent tools for the digitization, development and teaching of African languages. Since 2019, our association is supported by 20 volunteers from various fields, several partnerships were signed (universities, the African continent faces the issue of safeguarding and enhancing its cultural and linguistic inheritance. Created in 2017, the NTeALan project aims at setting up intelligent tools for the digitization, development and teaching of African languages. Since 2019, our association is supported by 20 volunteers from various fields, several partnerships were signed (universities, institutions, startups, association) and we have implemented several prototypical applications: chatbots, collaborative dictionary, linguistic map, REST APIs for African language resources. With its multimedia center dedicated to NLP, NTeALan aims at making African languages a cornerstone of Africa's cultural, linguistics and technological development.
Keywords: African Research